2008
DOI: 10.1002/joc.1668
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatic variability across the Susquehanna River Basin, USA, since the 17th century

Abstract: ABSTRACT:The Susquehanna River Basin (SRB) is an extensive river drainage network that covers a total of 71 228 km 2 in portions of New York, Pennsylvania, and Maryland, with more than 4 million inhabitants. It is the major source of fresh water to the USA's largest estuary, the Chesapeake Bay. Therefore, the hydroclimatic conditions within the SRB affect a large human population in addition to the ecological health of one of the world's most complicated and important estuarine environments.This research proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…The teleconnection variables showed a similar explanatory power (with an R-squared value of up to 22%) over the 53-yr period to that obtained by Griffiths and Bradley (2007) and Leathers et al (2008), who used similar time periods. However, little explanatory power was obtained for the indices over 103 ears.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The teleconnection variables showed a similar explanatory power (with an R-squared value of up to 22%) over the 53-yr period to that obtained by Griffiths and Bradley (2007) and Leathers et al (2008), who used similar time periods. However, little explanatory power was obtained for the indices over 103 ears.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies of temperature and precipitation in the United States have linked climatic variability to a number of large-scale forcing mechanisms, such as the El Niñ o-Southern Oscillation (ENSO) and the Arctic Oscillation (AO) (Griffiths and Bradley 2007;Leathers et al 2008). While a comprehensive analysis of the effect of such mechanisms is beyond the scope of this study, an exploratory analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
“…For the 11 Nunavut weather stations with continuous or close to continuous data from 1946 to 2015 (Figure ), we extracted monthly mean temperatures directly from Environment Canada's national climate data archive (Environment Canada, ) or calculated monthly mean temperatures from Environment Canada's daily temperature archive data. In some instances, the monthly temperatures were missing from the Environment Canada data and, in these cases, we hindcast or reconstructed the monthly mean temperature using data from the closest weather station (Leathers, Malin, Kluver, Henderson, & Bogart, ; Panchen & Gorelick, ; Panchen et al., ; Throop, Smith, & Lewkowicz, ). The latitude, longitude, and elevation of the weather stations have not changed over the 70‐year period.…”
Section: Methodsmentioning
confidence: 99%
“…Because of a lack of existing research and a scarcity of local climate records prior to 1900, few estimates exist of the impact of the acute deforestation in the SRB on its climate and hydrology. Leathers et al (2007) investigated the hydroclimatological history of the SRB and explored the role of land cover changes on the regional climate. They found that the SRB did not respond strongly to any of the major hemispheric-scale forcing mechanisms thought to affect the climate of eastern North America.…”
Section: Introductionmentioning
confidence: 99%